Penerapan Kajian Arsitektur Hijau dalam Strategi Perancangan Terminal Bus dan Pusat Perbelanjaan di Kabupaten Karanganyar - Russiana Wahyu Uslifah Safrina; Agung Kumoro Wahyuwibowo; Maya Andria Nirawati (ARSITEKTURA, 2019)
Land transportation, especially buses, plays an important role in community activities. The number of people who use buses will increase the number of buses. With the increase in the number of buses, a bus station that can accommodate adequate fleets and passengers is needed. In Karanganyar District there are 10 bus stations available but none of them are able to accommodate passengers and fleets with adequate facilities. The Government of Karanganyar has planned the development of the 2013-2032 Karanganyar Spatial Plan in the form of bus stations. One of them is located in Kebakkramat Sub-district. Bus station optimization can be combined with the existence of a shopping center as a support for activities and can be utilized by the people in surrounding areas to fulfill their needs. Bus stations and shopping centers are public facilities with high vehicle intensity and located in industrial locations which cause pollution. The green architecture approach is used as a design strategy to overcome problems and increase public awareness of the importance of caring for the environment. From this phenomenon, literature and field data are collected. Then, they are analyzed and discussed in accordance with the principles of green architecture based on criteria and benchmarks of the Green Building Council Indonesia. It is conducted to be applied to the selection of site locations, green architecture in building design, and utility systems.